1979
DOI: 10.1080/03014223.1979.10428397
|View full text |Cite
|
Sign up to set email alerts
|

Larval development of the cockleChione stutchburyi(Bivalvia: Veneridae) reared in the laboratory

Abstract: Larvae of the New Zealand cockle Chione stutchburyi (Wood, 1828) reared to settlement in the laboratory are described. They are characterised by dissimilar shoulders with a large, broadly rounded anterior shoulder and end, and broadly rounded umbo, typical of the Veneridae. Setting occurred after 20 days at a minimum length of 180 pm. Shell dimensions increased linearly during larval development but hinge length did not. The L:H ratio decreased from 1.27 at L = 100 to 1.1 at L = 200 and .the L:D ratio from 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Spawning typically occurs in the warmer summer months, with peak spatfall previously observed in Whangarei Harbour between December and February (Lundquist & Broekhuizen 2012). The dispersal period lasts 2 to 3 wk, after which settlement occurs at a size of approximately 180 µm (Stephenson & Chanley 1979). The shell of infaunal bivalves is entirely composed of aragonite, with calcite not being deposited (Green et al 2013).…”
Section: Study Speciesmentioning
confidence: 99%
“…Spawning typically occurs in the warmer summer months, with peak spatfall previously observed in Whangarei Harbour between December and February (Lundquist & Broekhuizen 2012). The dispersal period lasts 2 to 3 wk, after which settlement occurs at a size of approximately 180 µm (Stephenson & Chanley 1979). The shell of infaunal bivalves is entirely composed of aragonite, with calcite not being deposited (Green et al 2013).…”
Section: Study Speciesmentioning
confidence: 99%
“…Peak spawning occurs in austral summer (January to april) and peak spatfall is observed between February and may (Stephenson & Chanley 1979). The larval period is estimated at 2-3 weeks (Stephenson & Chanley 1979;Strathmann 1987), with settlement at a size of approximately 180 µm (Stephenson & Chanley 1979). Cockles exhibit postsettlement movement primarily via bedload dispersal (Turner et al 1997;Lundquist et al 2004a), and adults have been observed crawling through surface sediments at rates of up to 1.3-1.7 m per day (hewitt et al 1996).…”
Section: Study Speciesmentioning
confidence: 99%
“…Peak spawning occurs in austral summer (January to april) and peak spatfall is observed between February and may (Stephenson & Chanley 1979). The larval period is estimated at 2-3 weeks (Stephenson & Chanley 1979;Strathmann 1987), with settlement at a size of approximately 180 µm (Stephenson & Chanley 1979).…”
Section: Study Speciesmentioning
confidence: 99%
See 2 more Smart Citations